Optical head alignment method using serial manipulators for maskless lithography system - Choi, Jong Yoon; Park, Sae Whan; Ihn, Yong Seok; Choi, Hyouk Ryeol; Moon, Hyungpil; Koo, Ja Choon (SPRINGER HEIDELBERG, 2015)
As the cost of photomasks for lithography processes becomes prohibitive especially for large size panel displays, researchers have been developing maskless alternatives using various physical wave sources. Despite the prominent overall manufacturing cost reduction benefit, the maskless lithography system has drawbacks in some respects. These issues include productivity, size of the system, and lithography hardware cost efficiency. One of the well accepted solutions is massive parallel exposure using multioptical heads. In order to implement the multi heads option, securing accurate alignment of the heads is essential. In this paper, an alignment algorithm of a spot array manipulated with serial mechanism is suggested. The suggested method enables to reduce the overall error using the genetic algorithm. Defining spot array error as fitness function of the algorithm is introduced. And correlation with kinematics of the optical system and spot array error will be represented. In addition, 4 DOF serial manipulator design and its kinematic analysis is presented. Finally, the developed system is tested and evaluated. The suggested algorithm allows spot array error to be reduced about 80 % with regards to random error. This paper contributes to accurate alignment of the heads by suggesting an alignment algorithm of a spot array manipulated with a serial mechanism.